Geochemistry characteristics and dolomitization mechanism of the Upper Cambrian dolomite, eastern Ordos Basin, China. (10th July 2019) - Fu, Siyi; Zhang, Chenggong; Chen, Hongde; Qing, Hairuo; Chen, Anqing; Zhao, Junxing; Su, Zhongtang; Hao, Zhemin
Abstract : There are widely developed carbonate formations in the lower Palaeozoic, Ordos Basin, China. However, previous studies have paid more attention to the Ordovician formations and largely ignored the Cambrian formations, which also have a larger sediment thickness. Recently, with the continuous discovery of dolomite gas fields in the Ordovician Majiagou formation, more investigations have begun to focus on the deeper dolomite in the Cambrian Sanshanzi Formation (Є3 s). This study looks into the origin of the dolomite through a combination of petrology, major–trace elements, and stable isotope and rare earth element (REE) analysis of samples from five outcrops. The results show that the main dolomite types in the study area are dolarenite (Type 1), micrite‐fine crystalline dolomite (Type 2), and medium crystalline dolomite (Type 3). The δ 13 C values and δ 18 O values of each dolomite formation are close to those of seawater‐derived dolomite and have slightly higher Na 2+ concentrations, suggesting that dolomite formation is closely related to the denser seawater. The REE compositions are characterized by enrichment for light REEs and depletion for heavy REEs, exhibiting an apparent negative Eu anomaly and a slight negative Ce anomaly, indicating that the dolomites of the Є3 s may form in a weak‐reduction to the weak‐oxidation environment. The total REE (ΣREE) concentrations of Type 3 dolomites are lower than other types, suggesting that those dolomites may mean that the REEs are lost during the diagenesis. Type 1 dolomite has lower MgO and CaO values and a higher Mn 2+ concentration than the other two types of dolomites, indicating that Type 1 dolomite suffered the action of atmospheric fresh water. Type 2 dolomite has lower Mg and Ca values than Type 3 dolomite, suggesting that Type 3 dolomite has a higher dolomitization degree. Further study into the combined palaeogeographical background confirms the dolomitization model of the study area: Type 1 and Type 2 dolomites may have been formed by penecontemporaneous or seepage–reflux dolomitization during early‐stage diagenesis. Subsequently, stratigraphic uplift lead to the Type 1 dolomite suffering the action of atmospheric fresh water, but there was no dorag dolomitization. Type 2 dolomite became the main dolomite type by seepage–reflux dolomitization in this period. Later, Type 2 dolomite was converted into Type 3 dolomite during progressive burial.